(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In the current globalized world, engineering and technology education is considered incomplete if you are not learning any foreign language. Some of the primary reasons for this has been the extensive network of multinational companies in different parts of the world and the broader scope of going for higher studies in different universities across the world. Considering all these points, learning a foreign language has been made mandatory for all the engineering students in VIT. Spanish is one of the foreign languages which many of the engineering students in VIT prefer to learn.While learning Spanish, Duolingo app or website is used as a part of one of the digital assignments in my classroom because technology has made its way into language learning. Although there are several language learning apps or websites for self-study, I have used Duolingo with my students because of its effectiveness and free availability to all without any subscription fee. This research paper will look into one of the important questions, and that is Will making ‘Duolingo’ as part of digital assignment help students improving Spanish and finally performing better in their Final semester exam of Español Fundamental ESP1001?In this paper, the research is conducted among the students of Español Fundamental class in VIT who were learning Spanish. The study had 11 students who were all from BTech course but in different years. As a part of their digital assignment, all the students of the class were given ten topics to complete on Duolingo before a deadline after the conduct of the second continuous assessment Test (CAT 2). One of the prime objectives of this assignment was to make students practice and revise Spanish lessons and clear their doubts before sitting for the final assessment test of the semester. The goal of this study is to evaluate the effectiveness of Duolingo among eleven students whose average total score of CAT 1 and CAT 2 was less than fifty percent. The students’ performance was compared with the performance in the Final assessment Test after completing their digital assignment on Duolingo. The two conditions were compared in terms of gains on pre- and post-Duolingo assignment relevant to the particular course.